Positive effects of tactile massage for adolescents with Attention Deficit/Hyperactivity Disorder (ADHD) – A small scale study - Robertz, Anna-Carin; Törnhage, Carl-Johan; Nilsson, Stefan; Nyman, Viola; Kantzer, Anne-Katrin (Complementary therapies in clinical practice, 2024)
Epidemiological studies show the prevalence of attention deficit hyperactivity disorder (ADHD) in adolescents is around 5 %. There is strong evidence for psychosocial interventions and medication for treatment of ADHD core symptoms, but these alone do not always reach a satisfactory outcome. The aim of this small-scale study was to evaluate the impact of tactile massage on ADHD core symptoms in adolescents in a clinical setting. Secondary outcome measures addressed pain perception, ability to fall asleep, and stress levels before, during, and after the intervention. Fourteen adolescents aged 15–17 and previously diagnosed with ADHD received tactile massage sessions in an experimental, single-subject ABA study combined with a group-based evaluation using descriptive statistics. The adolescents and their parents answered questionnaires to follow up on the primary and secondary outcomes. The results showed a statistically significant reduction in hyperactivity/impulsivity and inattention, as well as oppositional defiant disorder (ODD). Participants reported that it was significantly easier to fall asleep. There was also a tendency to perceive less pain, but these results were not statistically significant. The compliance in this study was excellent. In this study, tactile massage appears to have had a significantly positive impact on ADHD core symptoms and the ability to fall asleep. The absence of adverse physiological changes and the excellent compliance, coupled with positive results, supports the idea that tactile massage may be considered safe and beneficial for adolescents with ADHD. Our findings need to be further investigated in future research. •Reduction in self-reported symptoms: hyperactivity and inattention.•Reduction of parent-reported hyperactivity, and oppositional defiant disorder.•Adolescents found it easier to fall asleep; some reported reduced pain.•Excellent compliance, no adverse effects, suggesting safety and benefits.•Findings support feasibility of a larger study on tactile massage for ADHD.